Desain Pembelajaran PAI di MAN Kota Surabaya Pasca Pandemi Covid-19 - Senata Adi Prasetia; Nur Rosida (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2022)
The article seeks to analyze the learning design of Islamic Religious Education (PAI) with the Briggs and Bela H. Banathy model at Madrasah Aliyah Negeri Surabaya. One of the essential aspects in the Islamic Religious Education (PAI) learning activities is learning design. Good learning design will have an impact on the quality of students and increase their competence. Through qualitative research based on field research with a case study approach and through in-depth interviews, this article shows three things, namely the design of Akidah Akhlak learning at MAN Kota Surabaya post Covid-19 Pandemic following the analysis model design of Briggs and Bela H. Banathy. The overall learning design is based on the Ministry of Religion and the Ministry of Education and Culture's 2013 Curriculum, KMA Numbers 183 and 184 of 2019 concerning Islamic Education and Arabic Language curriculum in Madrasas, which includes four elements: religious moderation, character education (PPK), anti-corruption education, and literacy improvement, and is adapted to the mission and vision of MAN Kota Surabaya.